1982
DOI: 10.1203/00006450-198206000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow in the Newborn Beagle Pup: the Germinal Matrix is a “Low-Flow” Structure

Abstract: SummaryThe newborn beagle pup serves as a model for neonatal intraventricular hemorrhage (IVH). Fluctuations in germinal matrix blood flow are felt to play a major role in the pathogenesis of IVH. We studied regional cerebral blood flow in awake newborn beagle pups utilizing [14CI-iodoantipyrine as a blood flow indicator and quantitative autoradiography. The equilibrium [tissue]:[bloodl partition coefficient for iodoantipyrine was 1.13 + .06 for grey matter.Blood flow was calculated for cerebral cortex (fronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1984
1984
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 9 publications
(14 reference statements)
0
7
1
Order By: Relevance
“…3). This contrasts with results of previous studies which showed no increase in white matter flow during hypoxia, in either the exteriorized fetal lamb or in the newborn puppy (6,30,32). These latter findings have been used to support the neuropathological observation of periventricular leukomalacia in infants who have suffered asphyxia1 brain injury.…”
Section: Cardiac Output (Mlomin-'kg Body-')contrasting
confidence: 57%
“…3). This contrasts with results of previous studies which showed no increase in white matter flow during hypoxia, in either the exteriorized fetal lamb or in the newborn puppy (6,30,32). These latter findings have been used to support the neuropathological observation of periventricular leukomalacia in infants who have suffered asphyxia1 brain injury.…”
Section: Cardiac Output (Mlomin-'kg Body-')contrasting
confidence: 57%
“…Moreover, careful evaluation o f two GM regions (GMMC and GMRC) reveals the following interesting characteristics: although baseline GMMC and GMRC blood flow is low and similar to blood flow in deep white matter regions, the blood pressure increment during hypertension is higher than deep white mat ter and similar to that seen in some grey mat ter structures. Thus, even though the GM is a 'low flow structure' under baseline condi tions [17], hypertension enhances GMMC and GMRC flow disproportionately when compared with deep white matter. Studies in littermate puppies (less than 24 h old) have shown that the GM capillaries have larger lumens, thinner walls, and are less well sup ported by perivascular stroma than capillar ies in cerebral cortex or caudate [22], Capil laries in cerebral white matter have prop erties intermediate between GM and grey matter.…”
Section: Discussionmentioning
confidence: 99%
“…Our methods have been extensively described in previous publications, and the details will not be repeated here [17,18,20], In brief, we measured regional cerebral blood flow (RCBF) in 17 puppies (12-60 h of age, 220-320 g). RCBF results from some of these puppies were previously reported [18].…”
Section: Methodsmentioning
confidence: 99%
“…Pasternak et al [16] provided evidence that the germinal matrix is, in addition, a low flow structure and may be particularly vulnerable to hypoxia and tis sue injury. Volpe [17] has suggested that hypoxia is the pivotal event that leads to circulatory failure, injury to the vascular endothelium, cerebral venous congestion, and, finally, IVH.…”
Section: Discussionmentioning
confidence: 99%